Mengenal Bisnis Yang Tak Kenal Rugi Dalam Perspektif Islam - Sukma Mehilda (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
This paper aims to discuss the concept of business in Islamic review. In Islamic teachings, Allah guarantees sustenance for his creatures. This belief in assurance is what encourages business people to keep trying even though they have failed repeatedly. This treasure is also believed to be a deposit from God which must be treated as a means to achieve the common good. In describing the relationship between man and God, it turns out that the Al-Quran uses many terms commonly used in the business world. The key to success in business is faith as a foundation in righteous deeds. The higher the success achieved, the greater the responsibility and benefits that are carried out.